The Economics of Conflicts: Natural Resources and The Dynamics of Conflicts in Post-Colonial West African Sub-Region - Blessing Ose Oligbi; Tunde Agara (International Journal of Economics Development Research (IJEDR), 2021)
Of all the sub-regions in Africa, the West Africa sub-region has become very notorious concerning conflict over natural resources. This has become rather endemic with virtually all the states making up the sub-region involved. Although the spate of conflicts has reduced somewhat over the years, especially with the interventionist policy of ECOWAS, however, the conflicts have presented us with domestic, regional as well as international dimensions. While it is crucial to understand the impact which these different trajectories have on the nature, dimensions, direction and dynamics of conflicts in West Africa, it is critical also to understand the role played by natural resources in both escalating and resolving conflicts in this area. While we are aware that, as at anywhere else in the world, these conflicts in the sub-region may be multidimensional and complex in nature, they nevertheless stem from socioeconomic, psychological, and political conditions internal to the respective nations. However, the paper argues that while the internal dimension can always be resolved among contenders, it become probably and takes longer time because of the external dimension which globalization has introduced. Thus, not only has globalization engendered new forms of conflict but it has also made certain that its resolution may not be possible and what we may be at best a reprieve.   Keywords: Conflicts, Dynamics, Globalization, Natural Resources, Sub-Region, West Africa .